THE RELATION OF CORRUPTION POTENTIAL PERCEPTION WITH BUSINESS INTEGRATION, PUBLIC INTEGRATION, AND LOCAL INTEGRATION SYSTEM (FROM CORRUPTION PERCEPTION SURVEY ANALYSIS) - Posma Sariguna Johnson Kennedy; Santi Lina (Asia Pacific Fraud Journal, 2020)
Potential of corruption is a condition that allows corruption criminal to occur. This paper aims to see whether perceptions of potential corruption have a relationship with business integrity, public integrity, and local integrity systems. The research method used is analysis by looking at the relationship between variables using Rank Spearman test. The results indicate that perceptions of potential corruption have relationship with local integration systems, local integration systems have relationship with the perceptions of business integrity, and the perceptions of business integrity have relationship with public integrity. Thus there are findings that, the eradication of corruption can not be initiated from public integrity, but must be initiated by the improvement of a clean system.